Revealing the Impact of Electronic Money and Economic Factors on the Velocity of Money in Indonesia - Margaretha, Viony; Wahyudi, Setyo Tri (Department of Development Economics, Universitas Sriwijaya, 2025)
The velocity of money is an important indicator that shows the efficient use of money in economic transactions. This study analyzes the effect of electronic money and economic factors such as GDP, interest rate, exchange rate, and composite stock price index on the velocity of money in Indonesia. The Error Correction Model (ECM) analysis method was used to estimate the equilibrium relationship in the short and long run using quarterly data for the period from 2016-2023. The findings indicate that in the long run, GDP, interest rate, and the composite stock price index have a positive and significant effect. Meanwhile, electronic money and exchange rate have a negative and significant effect on the velocity of money. On the other hand, the findings indicate that in the short run, GDP has a positive and significant effect on velocity of money. Whereas, electronic money, interest rate, exchange rate, and composite stock price index have no significant effect in the short run. These results imply that the government should support the expansion of electronic money systems to increase payment accessibility and efficiency, as well as maintain economic stability as fluctuations in economic factors significantly affect the velocity of money.